2007
DOI: 10.1016/j.humov.2007.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Control of velocity and position in single joint movements

Abstract: Previous research on single joint movements has lead to the development of models of control that propose that movement speed and distance are controlled through an initial pulsatile signal that can be modified in both amplitude and duration. However, the manner in which the amplitude and duration are modulated during the control of movement speed and distance remains controversial. We now report two studies that were designed to test and refine the pulse-step model of movement control. In our first study, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…Sanders [32] proposed two stages of response execution, namely, (i) response programming, which suggests logical control, and which seems to correspond to Costello's large-scale movement planning, and (ii) motor adjustment, which is supposed to produce "instructed muscle tension", in other words, it specifies the force required. This also seems to be in agreement with findings that the velocity and position control signals that are input to response execution are generally considered to be discrete and pulsatile [33].…”
Section: Control Of Humanssupporting
confidence: 91%
“…Sanders [32] proposed two stages of response execution, namely, (i) response programming, which suggests logical control, and which seems to correspond to Costello's large-scale movement planning, and (ii) motor adjustment, which is supposed to produce "instructed muscle tension", in other words, it specifies the force required. This also seems to be in agreement with findings that the velocity and position control signals that are input to response execution are generally considered to be discrete and pulsatile [33].…”
Section: Control Of Humanssupporting
confidence: 91%
“…A great deal of previous work on single-joint movements directed toward targets of varied amplitude has shown that acceleration amplitude (Sainburg and Schaefer, 2004b, Mutha and Sainburg, 2007), initial EMG peak amplitude (Corcos et al, 1989, Gottlieb et al, 1989, Gottlieb et al, 1990) or the initial amplitude of the time derivative of a force pulse (Ghez and Gordon, 1987, Gordon and Ghez, 1987a, 1987b)is specified prior to movement. In contrast, acceleration duration is modulated during the course of motion to correct for improperly specified amplitudes (Brown and Cooke, 1990, Cooke and Brown, 1990, Gottlieb, 1996, Mutha and Sainburg, 2007). In order to understand these control processes in more detail, Yadav and Sainburg (Yadav and Sainburg, 2011, 2014a) conducted simulations that combined two controllers in sequence: a predictive controller and an impedance controller.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these ideas have more recently gained support from empirical studies [36] [37] [38] [39] [40]. Predictive control mechanisms seek to optimize a combination of kinematic and dynamic costs of movement [8] [29] [36].…”
Section: Discussionmentioning
confidence: 99%